(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Cardiovascular diseases are the leading cause of death worldwide. Ischemic heart disease (IHD) dominates the scale of morbidity and is the main cause of disability of the population in Russia and other economically developed countries. The study of the causes of IHD group development leads to the isolation of a whole risk factor, most of which are included in the concept of "metabolic syndrome".